Contextual factors associated with evaluation practices of selected adult and continuing education providers in Malaysia - Shamsuddin Ahmad (Adult Education Research Conference, 1996)
Provided in this qualitative multiple case study are descriptions of how selected developmental agencies in Malaysia carried out program evaluation and what factors influenced the practice. Data were gathered from interviews with evaluation practitioners and from official documents. Evaluation practice of the agencies was not systematic nor comprehensive. Four contextual factors shaping the practice that emerged from the data are discussed.